Psychedelic Psychotherapy: Building Wholeness Through Connection. (11th February 2022) - Vaid, Gita; Walker, Barry
Background: We are confronted with dire statistics that document our current mental health crisis. New treatment modalities are desperately needed to address escalating mental suffering and trauma. Psychedelic medicines are attracting increased attention in psychiatry as effective treatment for a range of conditions. The mechanisms of actions and context necessary to maximize their full healing potential represent a radical departure from current psychiatric frameworks and present an opportunity to reimagine psychiatry as a healing art. Objective: Psychedelic psychotherapy leverages biological, psychological, and spiritual domains to harness innate healing potentials. A novel psychotherapeutic methodology utilizing psychedelic medicines as catalyzing agents is presented, one that provides a developmental model to promotes self-actualization. The paper outlines transformational psychotherapy, the therapeutic process and corresponding practice implications. Conclusion: Psychedelic psychotherapy represents a paradigm shift in healing, one that promotes self-integration and whole health. These shifts in internal health are correspondingly reflected in enhanced empathy, improved relatedness, and increased capacity for social connection. Much of human suffering and disregard for the planet is a reflection of our own collective inner impoverishment, fundamental disconnects, and unaddressed trauma. Psychedelic psychotherapy offers a healing approach to restore beauty and health to both the inner and outer worlds we inhabit.